(3MQR fGaY hMLGH OGaY dLejY GdRGHY hGdJhGHYs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje HSe Gddg HGHfG JHGQc MjWGffG jS SbbfG s
(3BNQgG (B:s
(3dg eYbHGJ ef Hjf jOjg hef Ndag jMaXhfg ef CeQ dGdg hdG jDOg MaXgeG hgh GdYdi GdYXje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdOcJhQ MSjf Ydi eMahX (B_ (3HZOGO (B(198) s
Keywords: (3GdeLGejYs